PENGARUH FAKTOR MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM DI BEI PASCAKRISIS EKONOMI GLOBAL 2008 - Dwi Bramantio; Fifi Swandari; Doni Stiadi (Universitas Lambung Mangkurat, 2015)
The purpose of this study is to analyze the influence of macroeconomic factors (interest rates, inflation rates, and the exchange rate) on the composite stock price index, the agricultural stock price index, and the mining stock price index. The method used in this study is a multiple linear regression analysis. Data obtained through Bank of Indonesia, Central Bureau of Statistics, and the Indonesia Stock Exchange. The sampling method is purposive sampling, and data are collected with the noted techniques. The results show that interest rates variable negatively affects to the composite stock price index and the agricultural stock price index, but has no impact on the mining stock price index. The inflation rate has no effect on the three indexes. Exchange rate negatively affects on the three indexes.